Terapia neuromotora intensiva nas habilidades motoras de criança com Síndrome de Down (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2018)
Assessing intensive neuromotor therapy in gross motor skills of a child with Down Syndrome